The Effect of Democratic Parenting on Self-Confidence in Adolescents - ., Nirmayanti; Siswanti, Dian Novita; Ansar, Wilda (Polteknik Ilmu Pemasyarakatan, 2023)
Low self-confidence in adolescents can affect the daily lives of adolescents. Self-confidence is formed from what children receive from home, especially from the care provided by parents as the first environment in a teenager's life. The purpose of this study was to determine the effect of democratic parenting on self-confidence in adolescents. This research uses quantitative research methods. The sampling technique used was purposive sampling. The respondents in this study were 208 people who fell into the categorization of dominant democratic parenting styles. The data collection technique in this study used a Likert scale, namely the scale of democratic parenting and self-confidence. The results of simple regression analysis show that there is an effect of democratic parenting on self-confidence in adolescents with a significance value of 0.000, p <0.05. The Rsquare value in this study is 0.129 which indicates that the contribution of democratic parenting to self-confidence in adolescents is 12,9%. This illustrates that the more dominant democratic parenting is applied by parents, the higher the self-confidence that adolescents have. The conclusion of this research is that parents and teenagers are expected to be able to establish good communication so that teenagers are more optimistic and responsible for themselves.